Effect of Leucine to Phenylalanine Substitution on the Nonpolar Face of a Class A Amphipathic Helical Peptide on Its Interaction with Lipid: HIGH RESOLUTION SOLUTION NMR STUDIES OF 4F-DIMYRISTOYLPHOSPHATIDYLCHOLINE DISCOIDAL COMPLEX - Mishra, Vinod K. (American Society for Biochemistry and Molecular Biology, 2008)
Model class A amphipathic helical peptides mimic several properties of apolipoprotein A-I (apoA-I), the major protein component of high density lipoproteins. Previously, we reported the NMR structures of Ac-18A-NH(2) (renamed as 2F because of two phenylalanines), the base-line model class A amphipathic helical peptide in the presence of lipid (Mishra, V. K., Anantharamaiah, G. M., Segrest, J. P., Palgunachari, M. N., Chaddha, M., Simon Sham, S. W., and Krishna, N. R. (2006) J Biol. Chem.281 ,6511 -651916407255). Substitution of two Leu residues on the nonpolar face (Leu(3) and Leu(14)) with Phe residues produced the peptide 4F (so named because of four phenylalanines), which has been extensively studied for its anti-inflammatory and antiatherogenic properties. Like 2F, 4F also forms discoidal nascent high density lipoprotein-like particles with 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC). Since subtle structural changes in the peptide-lipid complexes have been shown to be responsible for their antiatherogenic properties, we undertook high resolution NMR studies to deduce detailed structure of 4F in 4F·DMPC discs. Like 2F, 4F adopts a well defined amphipathic α-helical structure in association with the lipid at a 1:1 peptide/lipid weight ratio. Nuclear Overhauser effect (NOE) spectroscopy revealed a number of intermolecular close contacts between the aromatic residues in the hydrophobic face of the helix and the lipid acyl chain protons. Similar to 2F, the pattern of observed peptide-lipid NOEs is consistent with a parallel orientation of the amphipathic α helix, with respect to the plane of the lipid bilayer, on the edge of the disc (the belt model). However, in contrast to 2F in 2F·DMPC, 4F in the 4F·DMPC complex is located closer to the lipid headgroup as evidenced by a number of NOEs between 4F and DMPC headgroup protons. These NOEs are absent in the 2F·DMPC complex. In addition, the conformation of the DMPC sn-3 chain in 4F·DMPC complex is different than in the 2F·DMPC complex as evidenced by the NOE between lipid 2.CH and βCH(2) protons in 4F·DMPC, but not in 2F·DMPC, complex. Based on the results of this study, we infer that the antiatherogenic properties of 4F may result from its preferential interaction with lipid headgroups.